If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 = 4p + 3r Solving 27 = 4p + 3r Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. 27 + -4p = 4p + -4p + 3r Combine like terms: 4p + -4p = 0 27 + -4p = 0 + 3r 27 + -4p = 3r Add '-27' to each side of the equation. 27 + -27 + -4p = -27 + 3r Combine like terms: 27 + -27 = 0 0 + -4p = -27 + 3r -4p = -27 + 3r Divide each side by '-4'. p = 6.75 + -0.75r Simplifying p = 6.75 + -0.75r
| k^2-13k+37=-5 | | 5b-b-3b+1=20 | | B+4b-22=7b | | -5x^2+400x-2550=0 | | ln(x^5/x^3) | | H=6x(40-x) | | 16x^9-9x^7+20x^6= | | 18/3=x/4 | | 18/3=x/$ | | 2(w-7)=3w | | 14p+(-11p)-(-14)=2 | | p(x)=x^3+7x^2+17x-25 | | H=6t(40-t) | | 12k=-6(k+9) | | 5-(3x-6)= | | 6f+30+8=2f | | 22/24 | | 2x+4y+2=5 | | 5x-12=-7x | | 10+12y=2y-40 | | -r-(-9r)-20=-4 | | 2(x-1)-6x=26 | | 15/30 | | 19h-9h-9h+2=18 | | 25+30.76=3+5 | | 20-x=4x+5 | | 2g+3g-g-g=9 | | -1/5(×-25)=7 | | 6m-15=3m-36 | | 3-x=5x-9 | | 14u-14u+u=5 | | (70-4x)+(18x-8)=90 |